nvestigating the relationship between self-efficacy in clinical performance and psychological empowerment among nursing students - Fatemeh Moradi; Atefeh Vaezi; Vahideh Karimi (Zanjan University of Medical Sciences and Health Services, 2024)
Background: Clinical self-efficacy and psychological empowerment are two key factors in clinical nursing education. Objectives: This study was conducted to investigate the relationship between clinical self-efficacy and psychological empowerment (PE) in nursing students. Methods: This descriptive correlational study was conducted on 198 nursing students of the Zanjan University of Medical Sciences in 1402. The students were selected by census sampling. Data collection instruments included a demographic information form, the self-efficacy in clinical performance (SECP) questionnaire (designed and validated psychometrically by Cheraghi et al.), and Spitzer's Psychological Empowerment Instrument (SPEI). The data were analyzed using the independent samples student t-test, Pearson's correlation, and ANOVA in SPSS v.22 software. Results: Among the nursing students, the mean (SD) of the total SECP score was 108.7 (15.03), and the mean (SD) of the total PE score was obtained at 37.3 (5.8). The results showed that all dimensions of SECP showed a statistically significant correlation with PE in nursing students (P<0.001). Among demographic variables, SECP showed a statistically significant relationship with marital status and clinical experience. Also, PE showed a statistically significant relationship with the academic semester (P<0.05). Conclusion: Considering the direct correlation between SECP and PE among nursing students, as well as the importance of these parameters in achieving goals, managing stressors, and providing safe and quality care, nursing education program managers can adopt appropriate approaches to enhance the sense of independence and the ability to make correct independent decisions of nursing students in the clinical setting and during theoretical training courses, thereby increasing these students' clinical competency and enabling them to deliver quality clinical care and upgrade their clinical self-efficacy.